Unitarization of representations of a partially ordered set associated with a graph E_6 - Yakymenko, D. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
It is shown that any Schur representation of a poset associated with a graph E_6 can be unitarized with a certain character. The description of characters for which it is possible to unitarize the Schur representations of E_6 is presented.